2013
DOI: 10.1186/1471-2458-13-523
|View full text |Cite
|
Sign up to set email alerts
|

Family planning decisions, perceptions and gender dynamics among couples in Mwanza, Tanzania: a qualitative study

Abstract: BackgroundContraceptive use is low in developing countries which are still largely driven by male dominated culture and patriarchal values. This study explored family planning (FP) decisions, perceptions and gender dynamics among couples in Mwanza region of Tanzania.MethodsTwelve focus group discussions and six in-depth interviews were used to collect information from married or cohabiting males and females aged 18–49. The participants were purposively selected. Qualitative methods were used to explore family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
186
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(214 citation statements)
references
References 37 publications
24
186
1
3
Order By: Relevance
“…The findings of this study confirm the previous findings by Manyama (2016), Mosha (2013) and Mhando (2011) who found that the value of children in the Tanzanian families cannot be overemphasized. Children's value is linked to social and economic assistance in the families.…”
Section: Parents Without Childrensupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study confirm the previous findings by Manyama (2016), Mosha (2013) and Mhando (2011) who found that the value of children in the Tanzanian families cannot be overemphasized. Children's value is linked to social and economic assistance in the families.…”
Section: Parents Without Childrensupporting
confidence: 92%
“…The informants argued that the patriarchal system will continue to dominate because it is deeply rooted in the Tanzanian culture and has proved to maintain order (Male informant, 43 years, primary education, Kijitonyama). Similar observation on elevated mens' position in decision making in the Tanzanian families was also made by Mosha et al (2013), Mwageni et al (1998) and Rweyemamu (1999). Other informants also argued that egalitarian system will also flourish in the future because of increased opportunities to education, massive sensitization on gender equality altogether have some impact on the social organization of the Tanzanian societies (Female informant, 34 years, Diploma education, Kijitonyama).…”
Section: Authority Patternsupporting
confidence: 74%
See 1 more Smart Citation
“…The results also indicate that higher number of children was observed among those who had lower knowledge of their partners" ovulation dates. Notably, males who were interested in their spouse"s sexual health had lower household sizes than their counterparts 36,37 . Although the difference is not statistically significant in this study, linking it with results from other studies, points to a likely association between knowledge of a partner"s sexual health, controlled household sizes as well as practice of family planning -important statistics that demand due consideration when formulating reproductive health interventions or family planning and family spacing control policies.…”
Section: Discussionmentioning
confidence: 99%
“…Unintended pregnancies resulting from unplanned pregnancies are the consequences of poor contraceptive use in most developing countries 9 . Consequently, when faced with an unintended pregnancy, women may resort to an unsafe abortion if adequate safe abortion services are not available 6,10,11 . In Ghana, unmet need levels for family planning stands at 29.9% in recent 2014 Demographic Health Survey (DHS) results 12 .…”
Section: Introductionmentioning
confidence: 99%